2013
DOI: 10.1177/1461444813511038
|View full text |Cite
|
Sign up to set email alerts
|

Follow the leader! Direct and indirect flows of political communication during the 2013 Italian general election campaign

Abstract: This article evaluates the potential that Twitter affords politicians to communicate to citizens directly, through messages that they broadcast to users who follow them, and indirectly, to the extent that their followers autonomously re-circulate politicians’ messages to their own contacts. Analysis of more than 2 million accounts of followers of 10 national party leaders during the Italian 2013 general election campaign shows that most users are rather inactive and have very small followings. Moreover, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 23 publications
0
90
0
6
Order By: Relevance
“…In their study of Twitter-based opinion leadership in the Wisconsin recall election, Xu et al (2014) found that users' high centrality was positively related to the number of retweets received. Last, Vaccari and Valeriani (2013) studied 10 Italian politicians' followers throughout an electoral campaign, and Karlsen and Enjolras (2016) analyzed the number of mentions Norwegian electoral candidates received during the campaign. Their results are interesting since, in the case of Italy, the number of followers a politician had was not an indicator of his/her influence because the most followed politicians had the least active and followed users (Vaccari & Valeriani, 2013, p. 1).…”
Section: Opinion Leaders In Twitter Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study of Twitter-based opinion leadership in the Wisconsin recall election, Xu et al (2014) found that users' high centrality was positively related to the number of retweets received. Last, Vaccari and Valeriani (2013) studied 10 Italian politicians' followers throughout an electoral campaign, and Karlsen and Enjolras (2016) analyzed the number of mentions Norwegian electoral candidates received during the campaign. Their results are interesting since, in the case of Italy, the number of followers a politician had was not an indicator of his/her influence because the most followed politicians had the least active and followed users (Vaccari & Valeriani, 2013, p. 1).…”
Section: Opinion Leaders In Twitter Networkmentioning
confidence: 99%
“…In the case of the environmental movement in Milan, Diani (2003) found that having a clear public profile and access to the national media, a long tradition of campaigning and access to political institutions were also related to a high indegree. Vaccari and Valeriani (2013) detected that the more active and popular of Italian politicians' followers turned out to be famous sportspeople, pop culture celebrities, famous journalists, or high-profile politicians. Therefore, following metrics usually identify traditionally important and highly visible political or social players (Dubois & Gaffney, 2014;Vaccari & Valeriani, 2013).…”
Section: Opinion Leaders In Twitter Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an issue that academia has already begun to study (Giansante, 2015). Worldwide there are already many important studies related to electoral processes in a variety of countries, for example: the United States (Hendriks and Kay, 2010), Italy (Ceron & d'Adda, 2015;Vaccari & Valeriani, 2015), France (Mercier, 2015), Belgium (D'Heer & Verdegem, 2014) and Holland (Vergeer & Hermans, 2013), among many others. In fact, it is such a productive field that there are even compilations of the most important contributions (Vergeer, 2015).…”
Section: The New Communications Environment and Twitter's Role In Elementioning
confidence: 99%
“…Se trata de un extremo que ya ha comenzado a ser investigado por la academia (Giansante, 2015). En el ámbito internacional, contamos con ya con abundantes trabajos significativos ligados con procesos electorales en diversos países, por ejemplo respecto de EEUU (Hendriks & Kay, 2010;Vargo, Guo, McCombs & Shaw, 2014); Italia (Ceron & d'Adda, 2015;Vaccari & Valeriani, 2015); Francia (Mercier, 2015); Bélgica (D'Heer & Verdegem, 2014) u Holanda (Vergeer & Hermans, 2013); entre muchos otros. De hecho, se trata de un campo tan fructífero que podemos encontrarnos incluso con trabajos cuyo propósito es compilar las aportaciones más relevantes (Vergeer, 2015).…”
Section: El Nuevo Ecosistema Comunicativo Y El Papel De Twitter En Caunclassified